Methods of Islamic Religious Education for Children with Special Needs in Muslim Families in Banjarmasin, Indonesia - Hasanah, Mila; Afifah, Neela; Kuliyatun, Kuliyatun; Norliana, Norliana; Arba’iyah, Arba’iyah (Department of Special Education, 2024)
Children with Special Needs have different problems from children in general. They need special attention because of their limitations. Parents should pay attention to methods of Islamic Religious Education for Children with Special Needs to support children's development. The research method used is field research with a multi-site-based qualitative approach. The subjects in this study were 5 Muslim families from 5 sub-districts in the city of Banjarmasin, who had children with special needs in the mild category and had applied various methods of Islamic religious education and were accepted at the Inclusion State Elementary School in the city of Banjarmasin. The results of this study indicate that the Islamic religious education methods applied to children with special needs in Muslim families in Banjarmasin City are exemplary methods, advice, habituation, motivation and attention, punishment, communication-oriented, task analysis, direct instruction methods, and Method Prompts